2017
DOI: 10.1097/opx.0000000000001078
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Soft Contact Lenses in Children

Abstract: PurposeThere is increasing interest in fitting children with soft contact lenses. This review collates data from a range of studies to estimate the incidence of complications, specifically corneal infiltrative events and microbial keratitis, in patients under the age of 18 years.MethodsPeer-review papers were identified using PubMed and the Web of Science. A broad range of studies are summarized including large-scale epidemiological studies of contact lens–related complications, hospital-based case series, lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 45 publications
3
63
0
Order By: Relevance
“…In a recent review examining the safety of contact lenses in children, Bullimore reported the overall incidence rate of CIEs in children aged seven to 17 years as zero–335 per 10,000 years of contact lens wear . This is less than the reported annualised incidence of symptomatic CIEs in adults that ranged from 316–2,061 per 10,000 patient‐years . This relationship agrees well with the incidence of 97 per 10,000 years found by the CLAY study when they looked specifically at an eight to 12‐year‐old population .…”
Section: Risk Factorssupporting
confidence: 65%
See 1 more Smart Citation
“…In a recent review examining the safety of contact lenses in children, Bullimore reported the overall incidence rate of CIEs in children aged seven to 17 years as zero–335 per 10,000 years of contact lens wear . This is less than the reported annualised incidence of symptomatic CIEs in adults that ranged from 316–2,061 per 10,000 patient‐years . This relationship agrees well with the incidence of 97 per 10,000 years found by the CLAY study when they looked specifically at an eight to 12‐year‐old population .…”
Section: Risk Factorssupporting
confidence: 65%
“…However, this finding does not hold true for the youngest contact lens wearers. In a recent review examining the safety of contact lenses in children, Bullimore reported the overall incidence rate of CIEs in children aged seven to 17 years as zero–335 per 10,000 years of contact lens wear . This is less than the reported annualised incidence of symptomatic CIEs in adults that ranged from 316–2,061 per 10,000 patient‐years .…”
Section: Risk Factorsmentioning
confidence: 99%
“…These findings were confirmed by a comprehensive review of prospective studies of soft contact lens wear in young children 95 . Six published studies were identified with at least 150 patient years of lens wear reporting safety outcomes 18,72,82,108,126,127 .…”
Section: What Risks Are Associated With Myopia Control?mentioning
confidence: 77%
“…91 Although the latter may be theoretically possible with the off-label use of contact lenses in children, recent studies have shown that children do not have a higher risk than adults of suffering from contact lens-related complications with either OK 92,93 or soft contact lens wear. 94 Based on their relative safety profile [92][93][94][95] and significant levels of MC efficacy reported in the scientific literature, 13,15,17,96 OK and multifocal soft contact lenses appear to represent a viable MC treatment option for children.…”
Section: Regulatory Process For Marketing Medicalmentioning
confidence: 99%
“…There is evidence in the literature for certain devices having a role as being effective 12,13,17,96,129 and relatively safe [92][93][94][95] in reducing myopia progression. Ultimately, MC efficacy should be demonstrated in controlled clinical studies on human participants and confirmed by regulatory bodies to obtain marketing authorization or by independent research laboratories in case of off-label/unlicensed treatments, rather than basing claims of MC on extrapolation of results from animal studies or presumption of equivalence.…”
Section: Sources Of Off-label Use Information Permitted By the Fdamentioning
confidence: 99%